Artemyrianins A–G from Artemisia myriantha and Their Cytotoxicity Against HepG2 Cells - Tang, Shuang (Nat Prod Bioprospect, 2020)
ABSTRACT: Four new sesquiterpenoids, artemyrianins A–D (1–4), and three new norlignans, artemyrianins E–G (5–7), together with five known compounds (8–12), were isolated from the aerial parts of Artemisia myriantha (Asteraceae). The new compounds were established by spectroscopic data analyses (HRMS, IR, 1D and 2D NMR), and their absolute configurations were confirmed by the single-crystal X-ray diffraction or ECD calculations. The isolates showed cytotoxicity against HepG2 cells with IC(50) values ranging from 33.3 to 145.2 μM. GRAPHIC ABSTRACT: [Image: see text] ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s13659-020-00255-z) contains supplementary material, which is available to authorized users.